Animated Video Media as An Alternative to Developing Early Childhood Pre-Literacy - Sari, Novia Putri Mayang; Widyasari, Choiriyah (Universitas Muhammadiyah Surakarta, 2023)
Word This study focuses on developing early childhood pre-literacy in Tk Al Irsyad Al Islamiyyah Tawangmangu through animated video media to strengthen listening skills and fluency in oral language expression of what children see and hear. School planning uses the 2013 curriculum and the implementation of group learning, and teachers can evaluate children's achievements using age-appropriate STPPA (Child Development Achievement Level Standards) for 4-5 years. This research is both descriptive and qualitative. Data collection using observation techniques, interviews, and document reviews the validity of the data is obtained through data triangulation. The technique of analysing data is carried out with interactive models. The implementation of the use of animated video media in pre-literacy learning is implemented in group learning perception with steps: (a) concentration and focus, (b) orientation (looking around), (c) children's play stage, and (e) recalling/summary. The results of the study showed that animated video media is effective for developing early childhood pre-literacy, including the ability to listen and express spoken language from animated videos viewed by indicators and STPPA and show positive progress in every stimulation given. Learning using animated video media can stimulate early childhood preliteracy, and animated video media provides interesting learning and innovation.